2017
DOI: 10.1186/s13690-017-0228-2
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of trends and determinants of HIV/AIDS knowledge among the Bangladeshi women based on Bangladesh Demographic and Health Surveys, 2007–2014

Abstract: BackgroundSouth-Asian countries are considered to be a potential breeding ground for HIV epidemic. Although the prevalence of this incurable disease is low in Bangladesh, women still have been identified as more vulnerable group. The aim of this study is to assess the knowledge about HIV/AIDS: its trends and associated factors among the women in Bangladesh.MethodsWe analysed the nationally representative repeatedly cross-sectional Bangladesh Demographic and Health Surveys (BDHSs) data: 2007, 2011, and 2014. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 24 publications
19
37
0
Order By: Relevance
“…The present study also found that young women aged 20-24 years were more likely to have high overall knowledge about HIV/AIDS compared to adolescent girls aged 15-19 years. This con rms ndings of studies elsewhere [22,23]. The possible reason why adolescent girls have low overall knowledge about HIV/AIDS is limited access to health-related information.…”
Section: Discussionsupporting
confidence: 76%
“…The present study also found that young women aged 20-24 years were more likely to have high overall knowledge about HIV/AIDS compared to adolescent girls aged 15-19 years. This con rms ndings of studies elsewhere [22,23]. The possible reason why adolescent girls have low overall knowledge about HIV/AIDS is limited access to health-related information.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have revealed that comprehensive knowledge of HIV/AIDS was determined by age, 11 – 17 sex, 12 , 13 , 18 - 23 marital status, 18 , 20 , 22 educational status, 11 – 20 , 22 , 24 - 27 religion, 14 occupation, 13 , 15 , 18 media exposure, 19 , 23 , 26 , 27 household wealth index, 11 , 12 , 14 , 16 - 20 , 23 , 27 history of HIV test testing and counseling, 12 , 20 , 24 age at marriage, 19 history of multiple sexual partner, 20 place of residence, 11 , 12 , 14 , 16 – 20 , 27 and region. 12 , 16 , 26 …”
Section: Introductionmentioning
confidence: 99%
“…According to this study report, women who got media exposure have a higher likelihood of knowledge about HIV/ AIDS in both urban and rural area which is supported by preceding literatures. 7,8,29 The publicity to such media can interconnect knowledge and consciousness about HIV/AIDS through the tune, newscast information, theatres, and movies that can intensely affect the approach and behaviour of the public. 14 Besides, media can positively influence condom use practice during intercourse which can reduce HIV/AIDS risk.…”
Section: Discussionmentioning
confidence: 99%
“…5 Though Bangladesh is not in such an alarming state of HIV epidemic, the country has greater risk beacuse of several factors: the geographical imminense with India and Myanmer, top two severely HIV infected countries in this region, 6,7 gender disparity and poverty, drug trafficing and abuse, poor health-seeking behaviour and specifically, poor knowledge and awarenss about HIV/AIDS. 7,8 In 2018, nearly a million of Rohingya have eluded to Bangladesh after experiencing genocide in their native land Myanmar and a good amount of them were HIV positive which increases the risk at high level. 9 The infection proportions inside the susceptible clusters are growing, foremost, to an almost half likelihood that the worm will feast on the overall people.…”
Section: Introductionmentioning
confidence: 99%